Game Ular Tangga untuk Pembelajaran IPA - Sylvia, Sylvia; Wuryastuti, Sri; Suratno, Tatang (Didaktika, 2022)
This study Learning media is basically very important in the learning process. This is because learning media can make it easier for teachers to deliver subject matter and can create an effective and efficient learning process. The "Snakes and Ladders" board game media is one of the learning media that can make students more creative, active, and interested in following the course of learning. On the other hand, it can also create an effective and efficient learning process. The purpose of this research is to find out whether the snake and ladder board game media is suitable for use in learning and whether it can improve the science learning ability of "environmental change" material for fourth grade students in elementary schools in terms of the assessment of material experts and media experts. The second purpose of this study was to determine the student's response after using the snake and ladder board game media learning media product. The type of research mix method that is the embedded design is used in this research. This study shows the results: 1) Snakes and Ladders learning media is said to be suitable for use as a learning tool for fourth grade students in elementary schools. This is evidenced by the percentage level of validity of the learning materials from the expert validators of 83.9% on the ''A'' scale, the percentage of the validity of the learning media given by the media expert validators of 71.4% is on the “B” scale, and the percentage of responses students with a qualification of 87.5% with a score of 87.5% with an "A" scale qualification.